Relationship between National Culture and Development - Zuva, Tranos; Worku, Zeleke (Journal of Economics and Behavioral Studies, 2018)
Culture, as it is defined and well understood, differentiates one group from the other; in more general form, one country from the other. Culture then influences the behaviour and how we think in our everyday lives but so far culture of any group can only be measured in terms of a collection of cultural dimensions. This has made it difficult to establish whether there is any relationship between culture and any other social factors. In this study we derived national culture index from the four (4) Hofstede cultural dimensions (power (equality versus inequality), collectivism (versus individualism), uncertainty avoidance (versus uncertainty tolerance), masculinity (versus femininity)) using geo-mean formula. We then investigated whether there is any relationship between national culture index and national development index. In doing this we endeavoured to answer the question â€œIs There Really a Relationship Between Culture and Development?â€ posed by Mbakogu (2004:38). The data used for our experiments for Hofstedeâ€™s dimensions of national culture values were retrieved from Hofstede website that has an open licence for academic researchers. Data for human development national index were retrieved from UNDP website (Letter of consent was obtained from UNDP officials). The Pearson correlation coefficient was calculated (r=0.083, p=0.502>0.05), which indicated that there is very negligible positive relationship between cultural index values and the development index values. Since the value of p is greater than the significance level of 0.05, we concluded that there is inconclusive evidence about the significance of the association established between National Culture Index and National Development Index. Since we currently have a national culture index, researchers can now talk about culture as a homogeneous unit. Researchers may use the national culture index to investigate relationship between culture and any other social factors. In future we intend to use other cultural dimensions proposed by other researchers to present a national culture index.